Perceived Stress and Inflammatory Arthritis: A Prospective Investigation in the Studies of the Etiologies of Rheumatoid Arthritis Cohort. Issue 12 (6th November 2020) - Polinski, Kristen J.; Bemis, Elizabeth A.; Feser, Marie; Seifert, Jennifer; Demoruelle, M. Kristen; Striebich, Christopher C.; Brake, Stacey; O'Dell, James R.; Mikuls, Ted R.; Weisman, Michael H.; Gregersen, Peter K.; Keating, Richard M.; et al.
Abstract : Objective: The aim of this study was to determine the association of perceived stress with incident inflammatory arthritis (IA) defined as having at least 1 joint consistent with rheumatoid arthritis (RA)–like synovitis based on examination. Methods: We conducted a prospective cohort study in the Studies of the Etiologies of Rheumatoid Arthritis cohort. Participants without IA were recruited if they were a first‐degree relative of an RA proband or screened positive for anti–citrullinated protein antibody. Perceived stress was measured using the Perceived Stress Scale–14 (PSS‐14), in which scores can range from 0 to 56, and a higher score indicates greater perceived stress. The total PSS‐14 score, as well as 2 subscores indicative of perceived distress and self‐efficacy, were averaged across all study visits until development of IA or the last follow‐up. Hazard ratios (HRs) and 95% confidence intervals (95% CIs) of IA associated with average PSS‐14 scores were obtained using Cox proportional hazards models. Results: The mean total PSS‐14 score was 20.4. We found that a 1‐point increase in the perceived distress score was significantly associated with a 10‐percent increase in the risk of IA (adjusted HR 1.10 [95% CI 1.02–1.19]). Total PSS‐14 and self‐efficacy were not associated with IA risk (adjusted HR 1.05 [95% CI 0.99–1.10] and 1.04 [95% CI 0.91–1.18], respectively). Conclusion: An association between perceived distress and incident IA was observed in this at‐risk cohort. Replication of this finding in other preclinical and at‐risk RA populations is needed.